Efficacy and safety of ipragliflozin as add-on therapy to insulin in Japanese patients with type 2 diabetes mellitus (IOLITE): a 36-week, open-label extension of a 16-week, randomized, placebo-controlled, double-blind study - Ishihara, Hisamitsu (Diabetol Int, 2018)
OBJECTIVE: To examine long-term efficacy/safety of ipragliflozin, a sodium–glucose cotransporter 2 inhibitor, added to ongoing insulin therapy in Japanese patients with type 2 diabetes. METHODS: We conducted a 36-week, open-label extension of ipragliflozin therapy following a 16-week, randomized, placebo-controlled, double-blind period (treatment periods II and I, respectively). Prior to the open-label period, patients taking insulin with/without a dipeptidyl peptidase-4 (DPP-4) inhibitor were randomized to receive placebo or 50 mg once-daily ipragliflozin. Oral antidiabetic drugs other than DPP-4 inhibitors were discontinued 4 weeks before screening. Following treatment period I, all patients received open-label ipragliflozin 50 mg, with the possibility of a dose increase to 100 mg at week 24 if HbA1c was ≥ 7.0% at week 20. Efficacy endpoints were changes in HbA1c, fasting plasma glucose (FPG), self-monitored blood glucose, bodyweight, and metabolic hormones. Drug-related treatment-emergent adverse events (TEAEs) were monitored for safety. RESULTS: Of 175 patients randomized to ipragliflozin, 168 entered treatment period II, 121 (69%) of whom completed this period. The mean ± standard deviation changes in HbA1c, FPG, and bodyweight from baseline (start of treatment period I) to the end of treatment were − 0.83 ± 0.72%, − 31.5 ± 41.2 mg/dL, and − 1.34 ± 1.80 kg, respectively. Between weeks 8 and 32, HbA1c was lower in patients taking a DPP-4 inhibitor than in those without. The most common drug-related TEAE was hypoglycemia; no drug-related TEAEs not already reported for ipragliflozin were observed. CONCLUSIONS: Ipragliflozin was well tolerated, effective, and reduced bodyweight over a period of 52 weeks in patients treated with insulin with/without a DPP-4 inhibitor. CLINICALTRIALS.GOV IDENTIFIER: NCT02175784 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13340-018-0359-x) contains supplementary material, which is available to authorized users.